Akuntansi pendapatan kontrak konstruksi berdasarkan PSAK 115 tentang pendapatan dari Kontrak dengan pelanggan - Baiq, Krisnina Maharani Putri; Aptasari, Fety Widianti; Mujahidi, Khairul; Hastuti, Ely Windarti (Nur Science Institute, 2025)
This study aims to analyze in-depth how CV Yoranusa Abadi, as a construction company, recognizes revenue from its construction contracts with clients to provide specific services. The analysis is based on PSAK 115 concerning Revenue from Contracts with Customers. A qualitative research method with a descriptive approach is applied, with data collected through interviews, observations, and documentation. The findings indicate that CV Yoranusa Abadi has implemented the five stages of revenue recognition under PSAK 115 in all its construction projects. These stages include contract identification, identification of performance obligations, transaction price determination, transaction price allocation to performance obligations, and revenue recognition. Revenue is recognized and recorded based on the percentage of completed performance obligations agreed upon in the contract. This study can serve as an additional reference on how revenue recognition in construction companies aligns with the applicable accounting standards, namely PSAK 115